Habilidades sociales y clima social familiar en adolescentes de una institución educativa rural del Perú - Raymundo Castro, Yesica (2023)
The objective of the research was to analyze the relationship between social skills and family social climate in adolescents in a rural educational institution in Peru. The descriptive method and the survey technique were used with two instruments: Social Skills Evaluation Checklist (LEHS) and Family Social Climate Scale (ECSF). The study sample consisted of 62 students from first to fifth grade of the Santiago Ángel de la Paz Antúnez de Mayolo Gomero Educational Institution in the district of Acoria, Huancavelica. The results are: 77.42% of the adolescents have a low level of social skills, while 69.35% have a poor family social climate; for a significance level of 5% there is a very low positive correlation between social skills and family social climate (0.030). Therefore, it is concluded that family social climate is hardly positively associated with social skills